Race, poverty, and American tort awards: evidence from three datasets - Eric Helland; Alexander Tabarrok (Claremont McKenna College, Department of Economics, 2002)
We investigate the impact of the race and income of the jury pool on trial awards. We find that the average tort award increases as black and Hispanic county population rates increase and especially as black and Hispanic county poverty rates increase. An increase in the black countypoverty rate of 1 percentage point tends to raise the average personal injury tort award by 3 to 10 percent. An increase in the Hispanic county-poverty rate of 1 percentage point tends to raise awards by as much as 7 percent although this effect is less well estimated. These effects imply that forum shopping for high-poverty minority counties could raise awards by hundreds of thousands of dollars. Average awards fall with increases in white (non-black, non-Hispanic) poverty rates in two of our datasets, thus making these findings even more surprising. Awards increase with black and Hispanic county-poverty rates even after controlling for a wide variety of other potential causes.
Keywords: 330; Haftung; Zivilprozess; Rasse; Armut; Rechtsprechung; USA